2016
DOI: 10.3747/pdi.2013.00315
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Study Comparing a Single-Cuff Self-Locating Catheter with a Single-Cuff Straight Tenckhoff Catheter in Peritoneal Dialysis

Abstract: The study confirms the hypothesis that TCs have more malfunctions and a lower malposition-free survival rate than SLCs, and TCs are considered as the highest risk factor for malfunction during all study periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…The interventions introduced in the included studies were as follows: catheter type/configuration in 17 studies (36%) 14 30 with the most frequently studied intervention was comparing straight versus coiled intra-abdominal part of the catheters (9 RCTs). Insertion technique in 15 studies (32%) 31 45 with the most frequently studied intervention open versus laparoscopic catheter insertion (4 RCTs), two interventions in 3 studies (6%), 46 –48 and there were 6 other different interventions in 12 studies (26%) (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The interventions introduced in the included studies were as follows: catheter type/configuration in 17 studies (36%) 14 30 with the most frequently studied intervention was comparing straight versus coiled intra-abdominal part of the catheters (9 RCTs). Insertion technique in 15 studies (32%) 31 45 with the most frequently studied intervention open versus laparoscopic catheter insertion (4 RCTs), two interventions in 3 studies (6%), 46 –48 and there were 6 other different interventions in 12 studies (26%) (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Sanchez-Canel et al published a randomized study of 40 weighted versus 38 straight Tenckhoff catheters. Superior malposition-free survival rates and increased probability of malfunction in the Tenckhoff catheters (odds ratio 4.2) were seen, but this did not translate to a significant difference in survival (11). Early failure is most likely to be related to flow or catheter malposition compared with other complications.…”
Section: Discussionmentioning
confidence: 99%
“…Here it was shown, using a retrospective analysis, that complications were less frequent in the weighted group and dislocation of the catheters was 0.8% compared with 12.0% in Tenckhoff catheters. Two trials comparing open weighted versus open non-weighted and straight Tenckhoff catheters showed improved catheter survival in the weighted group (4) and less malpositions in the weighted group (10,11). Both studies did not consider factors that could influence catheter failure such as previous laparotomy and multiple previously failed catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent prospective randomized study compared catheter dysfunction in 40 incident PD patients using a single-cuff self-locating catheter and 38 patients using a single-cuff, straight Tenckhoff catheter (26). The study confirmed the hypothesis that Tenckhoff catheters have more malfunctions and a lower malposition-free survival rate than self-locating catheters.…”
Section: The Self-locating Pd Cathetermentioning
confidence: 99%
“…The study confirmed the hypothesis that Tenckhoff catheters have more malfunctions and a lower malposition-free survival rate than self-locating catheters. In particular, multivariate logistic regression analysis indicated an increased probability of malfunction with the use of Tenckhoff catheters (OR = 4.5) (26).…”
Section: The Self-locating Pd Cathetermentioning
confidence: 99%